The Search For Personal Identity In Khaled Hosseini'sAnd The Mountain Echoed (2013): A Psychological Approach - Kurniawati, Ika Agustina, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
The aim of this research is to analyze searching for personal identity reflected in Khaled Hosseini's And The Mountain Echoed novel. The objective of the study is to analyze the structure elements of the novel and to analyze the major character step to search her personal identity based on psychologycal approach. The research is qualitative research. The method to analyze the data is descriptive analysis. The object of the research is Khaled Hosseini's And The Mountain Echoed novel and the writer analyzes the novel by using psychological approach. Based on psychological analysis it can be concluded that the ignorance of individuals for themselves make people need to know their real self. The story illustrates the psychological phenomena in which individual searches her personal identity.It tells that the main character does not know much about herself and she feels that her life is like a puzzle. Hosseini describes the self concept experienced by major character to search for her true identity.